ANALISIS PROSEDUR PELAYANAN ADMINISTRASI TERHADAP WAKTU TUNGGU PASIEN RAWAT JALAN DI POLI UMUM PUSKESMAS MATARAM TAHUN 2024 - Aidil Fitriana, Imelda Yanti; Lale Ajeng Khalifatun Wardani; Muhammad Habibullah Aminy; Slamet Mardiyanto Rahayu; Fathurrahman; Muhammad Aditya Rachman (Nusadaya Journal of Multidiciplinary Studies, 2024)
Waiting times for services at the Mataram Community Health Center, both at the registration counter and in the general clinic, generally meet the standards set by the Indonesian Ministry of Health. Most respondents expressed satisfaction with the waiting times they experienced, both during registration (10–15 minutes) and while waiting for services in the general clinic (≤30 minutes). Fifty-six percent of respondents responded positively to the waiting time at the registration counter and 54% to the waiting time in the general clinic. This indicates that the majority of patients have a positive perception of the efficiency of the service provided. However, a small number of patients remained dissatisfied, for reasons possibly related to the workload of medical staff, the queuing system, or service times during peak hours.